Pelatihan Pengembangan Usaha Pada Koperasi Modern yang Bergerak di Sektor Pangan - Mulyana, Iwan; ARR, Tryiis (LPPM Universitas Koperasi Indonesia, 2025)
Cooperatives play a strategic role in community-based economic development in Indonesia, particularly in the food sector. However, the dynamics of the digital era and globalization demand cooperatives to transform into modern and highly competitive entities. This paper outlines several topics covered in the training, including Selecting Alternatives and Assessing Investment Feasibility, Cooperative Financial Planning and Budgeting, and Developing a Business Feasibility Study. The training involved 30 participants from various food sector cooperatives in West Java, employing a participatory, educational, and applicative approach. The results indicate an improvement in participants' understanding of Investment Feasibility, Cooperative Financial Planning and Budgeting, and Developing a Business Feasibility Study. While the training effectively enhanced participants' capacity, challenges such as limited technological infrastructure and human resources remain obstacles. This training contributes to strengthening participants' skills, promoting digital transformation, and improving the competitiveness of food sector cooperatives. For sustainability, post-training assistance, the development of advanced training programs, and collaboration among cooperatives are recommended